Performance of Some Introduced Hybrid Cotton (Gossypium hirsutum) Varieties in Bangladesh (The Agriculturists, 2012)
An experiment was conducted at the Regional Cotton Research Farm, Jagadishpur, Jessore during 2009-10 to evaluate six cotton varieties. Among them, four were hybrid cotton varieties and another two were inbreeds taken as control. Significant differences were found among the varieties for all traits except number of plants/ha and plant height at harvest. Hybrid variety SSC-3 performed well in terms of seed cotton yield (3570.33 kg/ha), lint yield (1404 kg/ha) and ginning out turn (GOT) percentage (43.83%). The highest 2.5% span length (31.44 mm) was found in hybrid HSC-4 and the lowest micronaire value of 3.87 mµ was found in hybrid SSC-2.DOI: http://dx.doi.org/10.3329/agric.v10i1.11059The Agriculturists 2012; 10(1): 10-15